Managing conflict of interest in the public sector a toolkit. - Whitton, Howard; Bertok, Janos; Organisation for Economic Co-operation and Development; ProQuest (Firm) (Paris, France : Organisation for Economic Co-operation and Development, 2005)
Managing conflicts of interest in both the public and private sectors has become a major governance issue world-wide. Identifying and resolving specific conflicts of interest can be difficult. This toolkit focuses on specific techniques, resources and strategies for identifying, managing and preventing conflict-of-interest situations more effectively and increasing integrity in official decision-making which might be compromised by conflicts of interest. It also provides non-technical, practical help to enable officials to recognize problematic situations and help them to ensure that integrity and reputation are not compromised. The tools themselves are provided in generic form. They are based on examples of sound conflict-of-interest policy and practice drawn from various OECD member and non-member countries. They have been designed for adaptation to suit countries with different legal and administrative systems.--Publisher description.
Introduction to conflict of interest management -- Conflict of interest management tools, listed by application -- Tool specifications.
"The toolkit was prepared by Howard Whitton in collaboration with Janos Bertok ..."--P. 3.
Also published in French as: Gerer les conflits d'interet dans le secteur public : mode d'emploi.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Public officers -- Professional ethics; Civil service ethics -- OECD countries; Conflict of interests -- OECD countries; Transparency in government -- OECD countries; Electronic books